the role of time management in facilitate the work requirements for employees of the administrative department at the ministry of higher education and scientific research - كاظم زينب كامل (Journal of Economics and Administrative Sciences, 2019)
The aim of the present study is to provide the adequate knowledge about the role of time management in facilitate the work requirements for employees of the administrative department at the Ministry of Higher Education and Scientific Research. The research depend on studying four important dimensions which are (time planning, time organization, time direction and time observation). In addition to study other five dimensions which are (new procedures, clear procedures, short procedures, the available information and the simplicity of the methods used).Questionnaire sheets consist of (38 questions) distributed to (170) employees and (146) sheets only were considered in the study. SPSS program was used for data analysis. The present studies conclude Time management is considered to be one of the most effective methods for effective and efficient management of organizations to be exploited best. A strong correlation was found between time management variables and workflow simplification variables, indicating a strong effect of time management variables in simplifying work procedures.